Lack of activity of HIV-1 integrase strand-transfer inhibitors on recombinase activating gene (RAG) activity at clinically relevant concentrations - Sally Demirdjian; Vincent N. Duong; Jennifer N. Byrum; Arabinda Nayak; Cooper B. McKinney; Jason K. Perry; Christian Callebaut; Karla K. Rodgers; Brie Falkard; Joy Y. Feng (Microbiology Spectrum)
ABSTRACT Human immunodeficiency virus 1 (HIV-1) infection remains a global health concern, with nearly 30 million people on antiretroviral (ARV) treatment. Integrase strand-transfer inhibitors (INSTIs) that block HIV-1 integrase are crucial components of first-line combination ARV therapies recommended in most international guidelines and have significantly improved HIV-1 treatment due to their efficacy and safety. This study evaluates potential off-target effects of INSTIs on recombinase activating genes (RAG1 and RAG2), which are essential for adaptive immune system function. We performed a comprehensive assessment of the off-target effects of clinically approved INSTIs on RAG activity, utilizing both biochemical and cellular assays. We purified the first catalytically active recombinant human core RAG1–RAG2 complex and tested it in the presence of the co-factor human HMGB1 protein for the gel-based biochemical RAG DNA cleavage assay. Additionally, we optimized an extrachromosomal V(D)J recombination cellular assay using murine mCherry-core RAG1, full-length murine mCherry-RAG2, and a plasmid substrate green fluorescent protein (GFP) reporter system, transfecting them into cells in the absence or presence of inhibitors. This setup enabled high-throughput analysis of V(D)J recombination for multiple compounds in a dose–response manner via flow cytometry. Physiologically relevant concentrations of INSTIs were examined for their potential impact on RAG activity and V(D)J recombination, with approved INSTIs showing minimal to no effects on recombinase activity. Consequently, the findings support the continued use of INSTIs in HIV-1 treatment without substantial concern for adverse effects on V(D)J recombination and immune system function.IMPORTANCEINSTIs are a crucial component of antiretroviral treatments for HIV-1 infection. This study provides a careful and thorough analysis of the impact of approved INSTIs on recombinase activating gene (RAG1 and RAG2) activity, which plays a pivotal role in the adaptive immune system. The concentrations tested were derived from several clinical studies and accounted for the maximum free fraction of the drug available in patients. This approach ensures that our findings are directly applicable to clinical scenarios by providing meaningful insights into the potential drug side effects in patients. We developed biochemical and cellular assays to measure the impact of INSTIs on RAG activity. All tested INSTIs did not inhibit RAG at supratherapeutic concentrations in the RAG1/RAG2 biochemical cleavage and cellular V(D)J recombination assays. Our assessment supports the continued use of INSTIs in HIV-1 treatments without concern for adverse effects.